HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN LARI 100 METER PADA SISWA KELAS XI SMAN 1 KULISUSU - Riswandi Nur; Muhammad Rusli; Abdul Saman (Journal Olympic (Physical Education, Health and Sport), 2022)
The purpose of this study was to determine the correlation leg muscle power with on speed running 100 meter ability at the students eleven class Senior High School 1 in Kulisusu. The population in this study was all of students eleven class Senior High School in Kulisusu which amounted to 320 peoples consisting of 140 sons and 180 daughters. sampling techniques by random sampling and the samling 20% from population with 140 sons and when sampling in this study was 28 peoples. The instrument to measure of the leg muscle power by using a stending board test, then to measure of the running 100 meter ability by using a speed running 100 meter test. Data analysis techniques using SPSS version 25 applications. The results obtained from the hypothesis test of limb muscle explosiveness have a relationship with the running speed of 100 meters, where rxy=0.38 at a significant level of 0.048<0.05, with a coefficient of determination of =0.142 or 14.2%. While 85.8 % is influenced by other factors such as flexibility, balance, strength, coordination, agility, and reaction. From the results obtained can be concluded that there is a significant relationship between the explosiveness of the limb muscles with a running speed of 100 meters in grade XI students SMAN 1 Kulisusu.